Beneficial effects of aluminum enrichment on nitrogen-fixing cyanobacteria in the South China Sea. Issue 1 (April 2018) - Liu, Jiaxing; Zhou, Linbin; Ke, Zhixin; Li, Gang; Shi, Rongjun; Tan, Yehui
Abstract: Few studies focus on the effects of aluminum (Al) on marine nitrogen-fixing cyanobacteria, which play important roles in the ocean nitrogen cycling. To examine the effects of Al on the nitrogen-fixing cyanobacteria, bioassay experiments in the oligotrophic South China Sea (SCS) and culture of Crocosphaera watsonii in the laboratory were conducted. Field data showed that 200 nM Al stimulated the growth and the nitrogenase gene expression of Trichodesmium and unicellular diazotrophic cyanobacterium group A, and the nitrogen fixation rates of the whole community. Laboratory experiments demonstrated that Al stimulated the growth and nitrogen fixation of C. watsonii under phosphorus limited conditions. Both field and laboratory results indicated that Al could stimulate the growth of diazotrophs and nitrogen fixation in oligotrophic oceans such as the SCS, which is likely related to the utilization of phosphorus, implying that Al plays an important role in the ocean nitrogen and carbon cycles by influencing nitrogen fixation. Highlights: Al stimulated the growth and the nifH expression of diazotrophic cyanobacteria. Al stimulated the growth and nitrogen fixation of C. watsonii in P-depleted medium. Al plays an important role in the nitrogen and carbon cycles in the ocean.